Public preferences for online medical consultations in China: a discrete choice experiment - Wang, Pei; Huang, Yuankai; Li, Haotao; Xi, Xiaoyu (Frontiers in Public Health, 2023)
Background Online medical consultation (OMC) is significant to promote the utilization and accessibility of healthcare resources and save time on consultation. However, the usage and public acceptance rates of it are still low in China. Meanwhile, few studies have focused on consumers’ demand of OMC services. This study aims to identify attributes that influence users’ preference for OMC services, quantify the value of these characteristics, and compare their relative importance. Methods A nationwide discrete choice experiment was conducted to survey Chinese residents’ preference choices for six attributes of OMC services. Conditional logit model and mixed logit model were used to analyze respondents’ preference. Willingness to pay and heterogeneity were estimated by the mixed logit model. Results A total of 856 respondents completed the study, and 668 questionnaires passed the consistency test. All of 6 attributes in the study were statistically significant except for “Doctor’s professional title – Associate Senior.” When choosing OMC services, respondents preferred to spend as little time and money as possible on a large online medical platform to consult a high-rated physician with a senior title from a well-known Grade-A tertiary hospital. Besides, respondents valued doctor’s evaluation score most and were willing to pay ¥107 to obtain the services of higher-scored doctors. Conclusion The study measured Chinese residents’ preferences for six attributes of OMC and showed the heterogeneity of attributes among subgroups. Our findings suggested that OMC services providers should reduce the customers’ waiting time, improve the quality of services and enhance professional skills to meet the customers’ requirements. More research on preferences for OMC needs to be conducted in China, especially for key populations such as patients with chronic diseases.